Measuring the Constructs of Sense of Place in Historical Area; A Review on Bazaar Neighborhood in Kermanshah - Mojtaba Lorzangeneh; Mohammad Masoud; Arezou Jamshidi Sheikhi Abadi (توسعه پایدار شهری)
A significant and determining factor in how a city's population or neighborhood residents feel is the sense of place. The dynamics of activities in the local context, the viability of inhabitants in the neighborhood, and boosting people's commitment to and sense of place boundary can all greatly benefit from paying attention to the indications and things associated with this emotion. This study used a developmental-applied nature, a quantitative approach, and a descriptive analytic method. The hypothesis of the research is that the construct of the sense of place in the Bazaar neighborhood due to its historical background is affected by the meaning. In order to measure the constructs of sense of place in the Bazaar neighborhood, which is located in the historical core and center of Kermanshah, the sample size was estimated to be 362 people using Cochran's formula and accounting for the error of 0.05. The structural equation model has been utilized to measure the research's dependent variables. The physical, meaning, and activity-dependent variables have been calculated in the model as the fundamental components of the sense of place in the Bazaar neighborhood in the historic core of Kermanshah. Amos Graphics (AG) software was also used to assess the research model in order to ascertain how each variable affected the development of a sense of place in the Bazaar neighborhood. The findings show that a sense of place in the Bazaar neighborhood is influenced by three factors the physical, activity, and meaning. This indicates that all of the signs were highly significant. It can be stated that the meaning component, which has a factor load of 0.997, has the most influence on establishing a sense of place in light of the structural equation model that was developed and its fit. A sense of place is least influenced by the activity component, with a factor loading of 0.967, and the physical component, with a factor loading of 0.915, in the Kermanshah Bazaar neighborhood.